Administrative regimentation and economic reform in China - Wolfgang Klenner (Intereconomics, 1990)
The West has scored an economic “victory” in Eastern Europe. In the Far East, on the other hand, developments appear to be slipping out of its hands: not only Japan but also, to an ever greater extent, South Korea and Taiwan have been growing into serious competitors in more and more sectors; China, meanwhile, evidently now has only a limited interest in economic cooperation with the West. What course will future economic policy in the People's Republic of China take?
Keywords: 330